Zinc metal carboxylates as potential anti-Alzheimer's candidate: in vitro anticholinesterase, antioxidant and molecular docking studies. Issue 3 (11th February 2021) - Zafar, Rehman; Zubair, Muhammad; Ali, Saqib; Shahid, Khadija; Waseem, Wajeeha; Naureen, Humaira; Haider, Ali; Jan, Muhammad Saeed; Ullah, Farhat; Sirajuddin, Muhammad; Sadiq, Abdul
Abstract: In search of suitable therapy for the management of Alzheimer's disease, this study was designed to evaluate metal complexes against its biochemical targets. Zinc metal carboxylates (AAZ1–AAZ6 ) were evaluated against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). The antioxidant in combination with anticholinesterase activity can be considered as an important target in the management of Alzheimer's disease. Therefore, these compounds were also screened for ABTS and DPPH free radical scavenging activity. In AChE inhibition assay, we noticed encouraging IC50 values of 33.07 and 59.52 µM for compounds AAZ5 and AAZ3, respectively. However, when we tested BChE activity, we observed an outstanding IC50 of 0.056 µM for compound AAZ6 . Amazingly all of our compounds (AAZ1–AAZ6 ) were proved to be strong antioxidants which actively supplement the anti-Alzheimer's activity. The majority of our compounds exhibited lower IC50 values than the standard ascorbic acid in both DPPH and ABTS assays. We also correlated our results with molecular docking studies. Results elaborated that AAZ1 and AAZ5 exhibit strong interactions with amino acids HIS 362, HIS 398, GLU 306 ARG 289 and SER 237 inside binding pocket of targeted protein. In remarks, we can claim that our synthesized zinc metal carboxylates have strong potency to manage Alzheimer's disease on both anticholinesterase and antioxidant targets. Communicated by Ramaswamy H. Sarma